Geotechnical site characterization using multichannel analysis of surface waves: A case study of an area prone to quick‐clay landslides in southwest Sweden. Issue 6 (25th August 2021) - Salas‐Romero, Silvia; Malehmir, Alireza; Snowball, Ian; Brodic, Bojan
ABSTRACT: Quick‐clay landslides are important geohazards in Sweden, Norway and Canada. While they have been studied using various geotechnical and geophysical methods, only a handful of seismic surveys have been reported for their studies. Here, we reprocess active‐source seismic data from a quick‐clay landslide site in southwest Sweden to complement earlier studies of reflection imaging and first‐break traveltime tomography with surface‐wave dispersion analysis. Results suggest extremely low shear‐wave velocities, even as low as 60–100 m/s. From a geotechnical perspective, this implies that the region classifies as a high‐risk zone for landslides and construction purposes. High or anomalous values of Poisson's ratio (or similarly P‐ and S‐wave velocity ratio) depict a zone within the normally consolidated sediments that likely represents a coarse‐grained layer, thus confirming earlier results from a number of boreholes drilled in the study area. Overall, the results presented further support to the previous hypothesis that the coarse‐grained layer plays a major role in the formation and creation of quick‐clay landslides in the study area. Additionally, an attempt to model the distribution of potential quick clays along one of the seismic profiles is performed through a combination of the modelled geophysical properties and soil textures. This study illustrates the potential of seismic methods, and how the integration of multiple geophysical properties and different data handling strategies can help to accurately characterize regions susceptible to quick‐clay landslides.